Epistemologi Pendidikan Hukum Islam dalam Menghadapi Tantangan Dekonstruksi Otoritas Keagamaan di Era Digital - Ari Arkanudin; Ulin Nuha; Ressi Susanti; Anggi Septia Nugroho (Bustanul Ulum Journal of Islamic Education, 2026)
This research is motivated by the shift in the paradigm of religious authority in the digital era, which has triggered a deconstruction of traditional scholarly hierarchies, where instant access to information often overlooks the need for methodological depth. This phenomenon poses a serious challenge to Islamic legal education, which has traditionally relied on sanad (chain of transmission) and institutional authority. The purpose of this study is to examine the epistemology of Islamic legal education in responding to these challenges and to map the scope of curriculum adaptation relevant to the dynamics of cyberspace. It employs a qualitative approach with library research, using the books and journals as primary sources, supported by relevant verses of Qur'an and their interpretation. Data were analyzed through content analysis. This results indicate that the epistemology of Islamic legal education needs to integrate bayānī (textual), burhānī (rational), and irfānī (intuitive/ethical) reasoning with critical digital literacy. The findings emphasize that confronting the deconstruction of authority is not achieved by isolating oneself from technology, but by reconstructing the role of educators from being the sole source of truth to becoming discourse facilitators capable of validating the originality of Islamic law amidst anonymous and fragmented information flows. This reorientation is crucial to ensure that the substance of Islamic law remains authoritative yet adaptive to the developments of the times